Hajj and Social Status: Self-Manifestation in Buginese Women - Nasruddin Nasruddin (Transformatif, 2022)
Hajj is one of the benchmarks of status in the socio-religious life of the Buginese people, the hajj symbol becomes a term that is used as a representation in the use of other symbols, through the behavior and manner of dressing used to refer to all symbols of hajj, especially in the behavior and dress of hajj in Buginese society. The purpose of this study was to reveal the impact of the hajj status obtained by Barru Buginese women as part of self-manifestation. This research was conducted in Soppeng Riaja District, Barru Regency. The research informants were women of Buginese Barru who had hajj status, public figures, and religious figures. The results of this study found that hajj status encouraged Barru Buginese women to feel valued and caused self-social prestige in the community.